Treatment with the natural FXR agonist chenodeoxycholic acid reduces clearance of plasma LDL whilst decreasing circulating PCSK9, lipoprotein(a) and apolipoprotein C‐III - Ghosh Laskar, M.; Eriksson, M.; Rudling, M.; Angelin, B. (Journal of internal medicine, 2017)
Background The natural farnesoid X receptor (FXR) agonist chenodeoxycholic acid (CDCA) suppresses hepatic cholesterol and bile acid synthesis and reduces biliary cholesterol secretion and triglyceride production. Animal studies have shown that bile acids downregulate hepatic LDL receptors (LDLRs); however, information on LDL metabolism in humans is limited. Methods Kinetics of autologous 125I‐LDL were determined in 12 male subjects at baseline and during treatment with CDCA (15 mg kg−1 day−1). In seven patients with gallstones treated with CDCA for 3 weeks before cholecystectomy, liver biopsies were collected and analysed for enzyme activities and for specific LDLR binding. Serum samples obtained before treatment and at surgery were analysed for markers of lipid metabolism, lipoproteins and the LDLR modulator proprotein convertase subtilisin/kexin type 9 (PCSK9). Results Chenodeoxycholic acid treatment increased plasma LDL cholesterol by ~10% as a result of reduced clearance of plasma LDL‐apolipoprotein (apo)B; LDL production was somewhat reduced. The reduction in LDL clearance occurred within 1 day after initiation of treatment. In CDCA‐treated patients with gallstones, hepatic microsomal cholesterol 7α‐hydroxylase and HMG‐CoA reductase activities were reduced by 83% and 54%, respectively, and specific LDLR binding was reduced by 20%. During treatment, serum levels of fibroblast growth factor 19 and total and LDL cholesterol increased, whereas levels of 7α‐hydroxy‐4‐cholesten‐3‐one, lathosterol, PCSK9, apoA‐I, apoC‐III, lipoprotein(a), triglycerides and insulin were reduced. Conclusions Chenodeoxycholic acid has a broad influence on lipid metabolism, including reducing plasma clearance of LDL. The reduction in circulating PCSK9 may dampen its effect on hepatic LDLRs and plasma LDL cholesterol. Further studies of the effects of other FXR agonists on cholesterol metabolism in humans seem warranted, considering the renewed interest for such therapy in liver disease and diabetes.